The Factors Affecting The Occurrence of Neonatal Respiratory Distress (RDN) in The Neonatal Intensive Care Unit at RSUD Undata - Iftitahurrohmah, Iftitahurrohmah; Abd. Rahman; Rosa Dwi Wahyuni; Rosmala Nur; Ratna Devi (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: In 2022, about 15% of infants treated in the NICU of RSUD Undata experienced respiratory distress neonatal (RDN), mostly related to preterm birth and neonatal infection. Objective: To identify factors influencing RDN in the NICU of RSUD Undata. Methods: A quantitative cross-sectional study conducted from August to October 2025 involving 43 mothers selected through purposive sampling. Univariate analysis described variable distribution, while logistic regression identified factors associated with RDN. Results and Discussion: Logistic regression showed a Chi-Square of 42.396 (p = 0.000), indicating that low birth weight (LBW), neonatal infection, gestational diabetes, and maternal age simultaneously affected RDN. Partially, LBW (p = 0.016), neonatal infection (p = 0.028), and gestational diabetes (p = 0.041) significantly influenced RDN, while maternal age (p = 0.417) did not. Conclusion: LBW, neonatal infection, and gestational diabetes significantly contributed to RDN, with LBW as the most dominant factor.